2021
DOI: 10.3389/fphy.2020.618320
|View full text |Cite
|
Sign up to set email alerts
|

An Activated Potassium Phosphate Fertilizer Solution for Stimulating the Growth of Agricultural Plants

Abstract: This study aimed to develop a sustainable industrial chemical engineering technology to improve the interaction between technology, plants, and soil in agriculture. The signaling crosstalk between H2O2 and NO and that between H2O2 and Ca2+ influence plant developmental and physiological processes. Many promising technologies for crop stimulation and protection are based on a thorough study of the environmental impact of various physical factors. A low-temperature, high-frequency plasma was generated via cathod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Previous experiments [ 37 , 38 ] on planting material processing with this type of PTS have shown that the result can vary over a wide range, up to the death of an object. It is important to find the concentration of PTS that is most effective for a particular biological object and the duration of its exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments [ 37 , 38 ] on planting material processing with this type of PTS have shown that the result can vary over a wide range, up to the death of an object. It is important to find the concentration of PTS that is most effective for a particular biological object and the duration of its exposure.…”
Section: Resultsmentioning
confidence: 99%
“…This method of fertilizing fields by supplementing potassium and phosphorus is simple but varies greatly in its effect on crops. In recent years, some scholars have also begun to try similar methods to obtain organic potassium phosphate fertilizers using different organic materials and minerals, supplemented with microbial agents [8,14,[39][40][41]. The results indicate that fermentation with a microbial agent greatly increase the soluble content of nutrients (K and P), suggesting that microbial fermentation can efficiently transform low-grade mineral rocks.…”
Section: Bomfs: a Current Needmentioning
confidence: 99%
“…Increasing the yield and improving the quality of agricultural products, reducing the costs of its production is impossible without the introduction of economically profitable and environmentally friendly technologies that ensure an increase in the productivity of agricultural plants. One of the promising directions in the creation of such technologies is the use of biologically activated water [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Usually, to obtain activated aqueous solutions, devices are used, the principle of operation of which is based on electrochemical methods using electrolyzers of various designs, including the separation of water into the constituents “anolyte” and “catholyte” [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%